Fundamental of Entrepreneurship ENT300: One Click Networking/ Nd Mohd Noraini Derun... [et al.] - Derun, Nd Mohd Noraini; Mohd Leo, Mohd Al Fitri; Bakrin, Jalaluddin; Ali Zaini, Mohd Azharani (2010)
The One Click Networking Centre is the business which offering networking and internet service. Our customer also can bring their laptop and use our internet service in our premise. This business is in the form of partnership, which consists of four partners. All partners have agreed to abide to all the terms of the partnership as contribute some capital according to the allocated shares. In a way, it proves that the reason why we have chosen partnership as our form of business in due to the act that we are able to share all profits as well as contribute ideas, knowledge and experience in order for the business to constantly achieve high productivity just as saying goes, “ Two heads are better than one’. This kind of business that provides such kind of services will attract the people in Desa Ilmu, Kota Samarahan. This is because Desa IImu is located near the institution places which are Universiti Teknologi Mara (UiITM) Sarawak,and Universiti Malaysia Sarawak (UNIMAS). Furthermore the increasing of residential area and housing area in Kota Samarahan which will increase the population in this area. Thus, students are the number one customer that we have targeted beside the other peoples.